2019
DOI: 10.1103/physreva.100.052329
|View full text |Cite
|
Sign up to set email alerts
|

Coherence-assisted non-Gaussian measurement-device-independent quantum key distribution

Abstract: Non-Gaussian operations on two mode squeezed vacuum states (TMSV) in continuous variable measurement device independent quantum key distribution (CV-MDI-QKD) protocols have been shown to effectively increase the total transmission distances drastically. In this paper we show that photon subtraction on a two mode squeezed coherent (PSTMSC) state can further improve the transmission distances remarkably. To that end we also provide a generalized covariance matrix corresponding to PSTMSC, which has not been attem… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 43 publications
1
16
1
Order By: Relevance
“…Such a discourse would be of immense interest to experimentalists in selecting the most optimal state for QKD based on transmission distances, noise robustness and/or coherence. While it has already been shown that a small amount of coherence is a actu-ally helpful process in the case of photon subtraction [40], we find that it is true for photon addition and catalysis too. This reinforces the idea that non-Gaussianity coupled with coherence leads to better performance in CV MDI QKD.…”
Section: Introductioncontrasting
confidence: 47%
See 3 more Smart Citations
“…Such a discourse would be of immense interest to experimentalists in selecting the most optimal state for QKD based on transmission distances, noise robustness and/or coherence. While it has already been shown that a small amount of coherence is a actu-ally helpful process in the case of photon subtraction [40], we find that it is true for photon addition and catalysis too. This reinforces the idea that non-Gaussianity coupled with coherence leads to better performance in CV MDI QKD.…”
Section: Introductioncontrasting
confidence: 47%
“…The latter has been studied in depth in Ref. [40]. The probability of n photon detections as a function of τ is plotted in Figs.…”
Section: B CV Mdi Qkd Using Non-gaussian Statesmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, it is worth noting that such a GSP operation can be easily implemented using linear optical devices and parametric down-converters [37]. Interestingly, the performance of continuous variable quantum key distribution can also be improved further using the TMSC instead of the TMSV [38]. Specially, larger coherence values are detrimental to the performance, but a small amount of coherence is more favorable for achieving maximum transmission distance.…”
Section: Introductionmentioning
confidence: 99%